Chlorophyll Catabolites in Senescent Leaves of the Plum Tree (Prunus domestica). Issue 11 (7th November 2016) - Erhart, Theresia; Mittelberger, Cecilia; Vergeiner, Clemens; Scherzer, Gerhard; Holzner, Barbara; Robatscher, Peter; Oberhuber, Michael; Kräutler, Bernhard
Abstract : In cold extracts of senescent leaves of the plum tree ( Prunus domestica ssp. domestica ), six colorless non‐fluorescent chlorophyll catabolites (NCCs) were characterized, named Pd ‐NCCs. In addition, several minor NCC fractions were tentatively classified. The structure of the most polar one of the NCCs, named Pd ‐NCC‐32, featured an unprecedented twofold glycosidation pattern. Three of the NCCs are also functionalized at their 3 2 ‐position by a glucopyranosyl group. In addition, two of these glycosidated NCCs carry a dihydroxyethyl group at their 18‐position. In the polar Pd ‐NCC‐32, the latter group is further glycosidated at the terminal 18 2 ‐position. Four other major Pd ‐NCCs and one minor Pd ‐NCC were identified with five NCCs from higher plants known to belong to the ' epi '‐series. In addition, tentative structures were derived for two minor fractions, classified as yellow chlorophyll catabolites, which represented (formal) oxidation products of two of the observed Pd ‐NCCs. The chlorophyll catabolites in leaves of plum feature the same basic structural pattern as those found in leaves of apple and pear trees. Abstract :